2020
DOI: 10.3389/fonc.2020.01727
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Esophageal Cancer: The Challenges and Opportunities for the Next Decade

Abstract: Esophageal cancer (EC) is the seventh most common cancer worldwide with over 570,000 new cases annually. In China, the incidence of EC is particularly high where approximately 90% of cases are defined as esophageal squamous cell carcinoma (ESCC). Although various risk factors have been identified, the knowledge of genetic drivers for ESCC is still limited due to high mutational loading of the cancer and lack of appropriate EC models, resulting in inadequate treatment choices for EC patients. Currently, surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 98 publications
0
124
0
Order By: Relevance
“… 6 , 7 Moreover, the dramatic development of immune checkpoint inhibitors, such as CTLA-4 and PD-1, suggests amazing therapeutic effects in clinical efficacy. 8 , 9 However, the therapy conditions are not eligible for most ESCC patients, which suggests that more studies on the molecular mechanisms’ elucidation and identifying useful biomarkers for immune checkpoint inhibitors are still urgently needed for cancer immunotherapy. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Moreover, the dramatic development of immune checkpoint inhibitors, such as CTLA-4 and PD-1, suggests amazing therapeutic effects in clinical efficacy. 8 , 9 However, the therapy conditions are not eligible for most ESCC patients, which suggests that more studies on the molecular mechanisms’ elucidation and identifying useful biomarkers for immune checkpoint inhibitors are still urgently needed for cancer immunotherapy. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Currently, most targeting therapies in cancer are directly targeted at activated oncogenes or “gain of function” genetic aberrations, including gene mutation, amplification, and fusion. However, there are very limited studies that have focused on esophageal cancer targeting therapy, most of which target epidermal growth factor receptor, and a very limited number of druggable hotspot mutations have been reported 12,40‐45 . Unfortunately, not all identified mutations or aberrant expressions can be directly targeted.…”
Section: Discussionmentioning
confidence: 99%
“…ESCC is the type of esophageal cancer predominant in East Asia, especially in China, where it accounts for more than 90% of cases [ 1 , 2 ]. It has been reported that there are more than 280,000 new cases of ESCC every year in China [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%